MANAJEMEN SARANA DAN PRASARANA DI MI TAHFIDZ ANWAHA - Ahmad Abdi; Ahmad Maulana; Akhmad Mubarak; Humaidi Humaidi; Syahrani Syahrani (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
Management of educational infrastructure, in this case as a tool in the teaching and learning process, is considered to have an influence on students' learning outcomes or achievements. Facilities are all the facilities needed in the teaching and learning process, both moving and immovable so that educational goals can be achieved smoothly, regularly, effectively and efficiently. Infrastructure is all kinds of equipment, equipment and objects used by teachers and students to facilitate the implementation of education. The method used in this research is a quantitative method. Quantitative research methods are a researcher's attempt to find knowledge by providing data in the form of numbers. Thus it can be concluded that the ownership status of facilities and infrastructure at MI TAHFIDZ ANWAHA belongs to the school which is in the high category. The facilities and infrastructure at MI TAHFIDZ ANWAHA are complete, including in the high category. The facilities and infrastructure at MI TAHFIDZ ANWAHA are good and standard, including in the high category. Maintenance of the facilities and infrastructure at MI TAHFIDZ ANWAHA is always carried out and this maintenance is carried out with educational excellence which is included in the high category. Facilities and infrastructure at MI TAHFIDZ ANWAHA may not be used outside school activities/hours and these facilities and infrastructure have been used according to their function, including in the very high category. The operational costs for facilities and infrastructure at MI TAHFIDZ ANWAHA come from BOS funds and sometimes there are problems in managing these operational costs which are in the high category.